Determination of Sun Protection Factor of Blemish Balm Nanocream Containing Avobenzone, Octyl Methoxycinnamate, and Vitamin C - M, Julianty S.; A, Arianto; Y, Yuandani (Asian Journal of Pharmaceutical Research and Development, 2020)
Objective: The aim of this study was to determine sun protection factor of blemish balm nanocream (BB nanocream) containing avobenzone, octyl methoxycinnamate and vitamin C. Method: The formulation of blemish balm nanocreams using a combination of a variety of concentrations of vitamin C (5, 7.5, and 9%), 3% avobenzone, and 7.5% octyl methoxycinnamate. The safety of the BB nanocream containing the highest concentration of vitamin C was examined using skin and eye irritation tests on the rabbit. SPF value of BB nanocreams determined by using UV-Vis Spectrophotometry method and compared with BB cream. Results: All BB nanocream containing vitamin C, avobenzone, and octyl methoxycinnamate did not irritate the eyes and skin of rabbits. The SPF value of BB nanocream containing a combination of 3% avobenzone, 7.5% octyl methoxycinnamate and vitamin C of 5, 7 and 9% were 18.0497, 21,0857, and 21.5883 respectively. The SPF value of BB nanocream without avobenzone, octyl methoxycinnamate and vitamin C was 10.4798 and bb krim was 15,8515. Conclusions: All BB nanocream formula containing 3% avobenzone, 7.5% octyl methoxycinnamate and Vitamin C (5%, 7%, and 9%) were not irritating the eyes and rabbit skin. The BB nanocream containing 3% avobenzone, 7.5% octyl methoxycinnamate and 9% vitamin C has the highest SPF value.